Choreic syndrome after cardiac surgery. Issue 12 (December 1988) - Robinson, R O; Samuels, M; Pohl, K R
Abstract : Five children had an acute choreic syndrome that started three to seven days after hypothermic cardiopulmonary bypass surgery. Improvement after an interval was seen in all, with complete resolution in two. In addition to the chorea, all children suffered complete supranuclear ophthalmoplegia, which has also shown subsequent improvement. Bulbar damage caused considerable speech problems. There was no cognitive impairment. Several drugs were tried without effect. Investigations of the cause, including histological examination, have been unrevealing.